FIRM LEVEL VALUATION DYNAMICS AND THE DETERMINANTS OF THE PRICE EARNINGS RATIO EVIDENCE FROM A BALANCED PANEL OF GLOBAL LARGE CAP EQUITIES 2005Q2 2025Q4 A FIXED EFFECTS PANEL ECONOMETRIC STUDY (World Economics and Finance Bulletin, 2026)
This study investigates the firm level determinants of the Price–Earnings ratio using a balanced quarterly panel of ten global large capitalisation equities observed over 84 quarters, from the second quarter of 2005 through the first quarter of 2026, yielding 840 firm quarter observations. The research is motivated by the persistent theoretical and empirical controversy over whether cross-sectional and time series variation in earnings multiples reflects rational expectations about future growth and risk, as predicted by the dividend-discount and residual income valuation frameworks, or whether it is better characterised by behavioural, liquidity-driven, and accounting-based anomalies documented since Basu (1977).